Adaptasi Masyarakat Terkait Pencemaran Lingkungan Di Tempat Pembuangan Sampah (TPS) Pancasila Kelurahan Lengkongsari Kecamatan Tawang Kota Tasikmalaya - Stefanny Tri Angelika; Indri Tri Hasanah; Nanda Nazam Masfufah Husna; Putri Fauziyyah M; Muhammad Fauzi Ramadhan; Yani Sri Astuti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Population growth that occurred in Tasikmalaya City in 2021 reached 731,606 people. Population density brings a number of problems, namely the problem of waste at the Pancasila TPS. Where the Pancasila TPS becomes a rubbish dump for the people around Pancasila who experience environmental pollution which has an impact on the people who live around the Pancasila TPS. The aim of this research is to determine the adaptation of the community around the TPS. The data collection techniques used in this research took the form of direct observation and interviews with the community around the TPS. The research results revealed that the form of adaptation carried out by the community around the Pancasila TPS was passive. The community can only surrender to environmental pollution around settlements, because the people around the Pancasila TPS are indifferent. Apart from that, the people around the TPS use well water to meet their daily needs. People do not take any action to reduce the pungent odor produced by air pollution because they are used to the smell. Therefore, they do not make changes to their residential buildings to reduce the penetration of odors into the house.